Reconstitution of the augmin complex provides insights into its architecture and function - Hsia, Kuo-Chiang (Nat Cell Biol, 2014)
Proper microtubule nucleation during cell division requires augmin, a microtubule-associated hetero-octameric protein complex. In current models, augmin recruits γ-tubulin, via its hDgt6 subunit’s C-terminus, to nucleate microtubules within spindles. However, augmin’s biochemical complexity has restricted analysis of its structural organization and function. Here, we reconstitute human augmin and show it is a Y-shaped complex that can adopt multiple conformations. Further, we find that a dimeric sub-complex retains in vitro microtubule-binding properties of octameric complexes, but not proper metaphase spindle localization. Addition of octameric augmin complexes to Xenopus egg extracts promotes microtubule aster formation, an activity enhanced by Ran-GTP. This activity requires microtubule binding, but not the characterized hDgt6 γ-tubulin-recruitment domain. Tetrameric sub-complexes induce asters, but activity and microtubule bundling within asters are reduced compared to octameric complexes. Together, our findings shed light on augmin’s structural organization, microtubule binding properties and define subunits required for its function in organizing microtubule-based structures.